2004
DOI: 10.1038/sj.ejhg.5201180
|View full text |Cite
|
Sign up to set email alerts
|

Association between schizophrenia and DRD3 or HTR2 receptor gene variants

Abstract: Schizophrenia is a severe and common psychiatric disorder afflicting 1% of the world population. A role of many neurotransmitter receptors in schizophrenia was suggested by an association with several polymorphisms located in their coding regions. In this study we examined the contribution of the T-102C and A-206G transitions in the 5-HTR2a and DRD3 receptor genes respectively to genetic susceptibility and phenotypic expression of schizophrenia disorder within the Greek population. We determined by PCR and RFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Although the association between the T102C polymorphism and MDD, BPD, and SCZ has been explored in many studies, the findings are inconsistent. Some studies have suggested that the T102C polymorphism is associated with susceptibility to MDD [Du et al, ; Li et al, ] and SCZ [Erdmann et al, ; Baritaki et al, ]; however, a number of studies failed to provide evidence to support these associations [Illi et al, ; Yosifova et al, ; Pakhomova et al, ]. As far as we know, a meta‐analysis confirming an association between the T102C polymorphism and MDD has not been published to date, and the meta‐analysis conducted by Seifuddin [] to investigate the T102C polymorphism and BPD did not give a definitive conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Although the association between the T102C polymorphism and MDD, BPD, and SCZ has been explored in many studies, the findings are inconsistent. Some studies have suggested that the T102C polymorphism is associated with susceptibility to MDD [Du et al, ; Li et al, ] and SCZ [Erdmann et al, ; Baritaki et al, ]; however, a number of studies failed to provide evidence to support these associations [Illi et al, ; Yosifova et al, ; Pakhomova et al, ]. As far as we know, a meta‐analysis confirming an association between the T102C polymorphism and MDD has not been published to date, and the meta‐analysis conducted by Seifuddin [] to investigate the T102C polymorphism and BPD did not give a definitive conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of association between HTR2A polymorphisms and schizophrenia have been published [Erdmann et al, 1996; Inayama et al, 1996; Williams et al, 1996; Baritaki et al, 2004]. These have mostly examined one to three polymorphisms each, of which a T/C polymorphism at position 102 (T102C) has been most frequently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Change in the levels of neurons such as dopamine and serotonin are identified in individuals with schizophrenia (Baritaki et al, 2004;Hirvonen et al, 2006). Psychological factors that make an individual more vulnerable to the onset of illness include being exposed to diathesis, which is related to the humoral (body fluids) theory of temperament and disease; the presence of schism, which means the parents are bitterly divided on most issues; and skew, which means there is an imbalance in the power relationship between the parents (Lidz, 1972); and familial patterns and double-bind communication (Bateson, 1978).…”
Section: Causes Of Serious Mental Illnessmentioning
confidence: 99%